2020
DOI: 10.1101/2020.08.12.248401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared and divergent phase separation and aggregation properties of brain-expressed ubiquilins

Abstract: The brain-expressed ubiquilins, UBQLNs 1, 2 and 4, are highly homologous proteins that participate in multiple aspects of protein homeostasis and are implicated in neurodegenerative diseases. Studies have established that UBQLN2 forms liquid-like condensates and accumulates in pathogenic aggregates, much like other proteins linked to neurodegenerative diseases. However, the relative condensate and aggregate formation of the three brain-expressed ubiquilins is unknown. We report that the three ubiquilins differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…To further determine the physiological relevance of UBQLN2 to tau homeostasis, we extended our analysis to tau transgenic mouse models. The intrinsic property of UBQLN2 to aggregate (Hjerpe et al, 2016;Sharkey et al, 2018;Gerson et al, 2021), combined with our results showing that UBQLN2 knockdown increased levels of wild-type tau, suggested that UBQLN2 aggregation might promote tau pathology. We also sought to determine whether tau pathology, in turn, could contribute to a cellular environment that enhances the tendency of UBQLN2 to aggregate and hence become dysfunctional.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…To further determine the physiological relevance of UBQLN2 to tau homeostasis, we extended our analysis to tau transgenic mouse models. The intrinsic property of UBQLN2 to aggregate (Hjerpe et al, 2016;Sharkey et al, 2018;Gerson et al, 2021), combined with our results showing that UBQLN2 knockdown increased levels of wild-type tau, suggested that UBQLN2 aggregation might promote tau pathology. We also sought to determine whether tau pathology, in turn, could contribute to a cellular environment that enhances the tendency of UBQLN2 to aggregate and hence become dysfunctional.…”
Section: Resultssupporting
confidence: 68%
“…In addition to sequestering other aggregating proteins, UBQLN2 itself is prone to aggregate and undergo liquid-liquid phase separation (LLPS) in vitro (Hjerpe et al, 2016;Dao et al, 2018;Sharkey et al, 2018). While both UBQLN1 and UBQLN4 share the ability to undergo LLPS with UBQLN2, the three UBQLN proteins diverge in liquid droplet characteristics and aggregation behavior, implying that, despite their similarity, functional differences may exist (Gerson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, pulldowns of K48-and K63-linked chains using GST-tagged UBQLN1, a close UBQLN2 homolog that also undergoes LLPS (Gerson et al, 2021), show that FL UBQLN1…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pulldowns of K48- and K63-linked chains using GST-tagged UBQLN1, a close UBQLN2 homolog that also undergoes LLPS (Gerson et al, 2021), show that FL UBQLN1 only interacts with longer K63-linked chains (Harman and Monteiro, 2019). However, UBQLN1 and UBQLN2 UBAs have no significant preference for either chain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 22, 2021. ; https://doi.org/10.1101/2021.04.21.440788 doi: bioRxiv preprint RTL8 binding to and nuclear recruitment of UBQLN2, RTL8 binding to UBQLN2 could modulate ubiquitin binding by UBQLN2. Intriguingly, all three UBQLNs undergo liquid-liquid-phase separation and are inherently aggregate-prone [52], and the UBA domain itself may seed UBQLN oligomerization and aggregation [22]. A systematic study of structural motifs and disease mutations in UBQLN2 will be required to determine which regions are critical for binding and whether fALS mutations impact RTL8 binding or RTL8-dependent properties of UBQLN2.…”
Section: Discussionmentioning
confidence: 99%